Ứng dụng công nghệ vi dòng chảy trong bào chế một số hệ nano mang thuốc - Trần, Thị Hải Yến (H. : ĐHQGHN, 2019)
Microfluidics is an emerging and promising interdisciplinary technology which offers powerful platforms for precise production of novel functional materials (e.g., emulsion droplets, microcapsules, and nanoparticles as drug delivery vehicles) as well as high-throughput analyses (e.g., bioassays and diagnostics). Microfluidics has recently appeared as a new method of manufacturing nanostructures, which allows for reproducible mixing in miliseconds on the nanoliter scale. This review first describes the fundamentals of microfluidics and then introduces the recent advances in making nanostructures for pharmaceutical applications including nano liposomes, polymer nanoparticles and nano polymerosomes